Sports training enhances visuo-spatial cognition regardless of open-closed typology - Chueh,Ting-Yu; Huang,Chung-Ju; Hsieh,Shu-Shih; Chen,Kuan-Fu; Chang,Yu-Kai; Hung,Tsung-Min (PeerJ, 2017)
The aim of this study was to investigate the effects of open and closed sport participation on visuo-spatial attention and memory performance among young adults. Forty-eight young adults—16 open-skill athletes, 16 closed-skill athletes, and 16 non-athletes controls—were recruited for the study. Both behavioral performance and event-related potential (ERP) measurement were assessed when participants performed non-delayed and delayed match-to-sample task that tested visuo-spatial attention and memory processing. Results demonstrated that regardless of training typology, the athlete groups exhibited shorter reaction times in both the visuo-spatial attention and memory conditions than the control group with no existence of speed-accuracy trade-off. Similarly, a larger P3 amplitudes were observed in both athlete groups than in the control group for the visuo-spatial memory condition. These findings suggest that sports training, regardless of typology, are associated with superior visuo-spatial attention and memory performance, and more efficient neural resource allocation in memory processing.
Keywords: Cognitive function; Sports; Expertise; Event-related potential